Strategy to Increase Reading Interest Through Literacy Culture Program in Students of SDN 21 Palembang - Rohmaniyah; Mefhi Isnaria (Quality : Journal Of Education, Arabic And Islamic Studies, 2026)
This study aims to analyze the effect of literacy culture programs on improving students' reading at SDN 21 Palembang. This research employs a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with the principal and homeroom teachers of grades 1 to 6, and documentation of literacy activities in the field. Data analysis used the Miles and Huberman model, comprising data reduction, data presentation, and conclusion drawing. The results show that literacy culture programs—specifically reading corner and reading clinic activities—significantly improve students' reading interest, especially among grade 4 and 5 students. This improvement is reinforced by active teacher support and parental involvement in accompanying children to read at home. Inhibiting factors include limited book collections, gadget influence, and insufficient parental participation. This research is expected to serve as a reference for educational practitioners in implementing literacy improvement strategies in elementary schools.